Employee Engagement Programmes As An Arena for Citizenship: A Case Study from Cadbury PLC - Cortes Ferreira, L (2009)
In their book ‘Corporations and Citizenship’ (2008), Crane, Matten and Moon suggest that the corporation could be an arena for different stakeholders’ citizenship. They detail varied possibilities, however do not empirically test any of them. This dissertation empirically evaluates this assumption, using Cadbury’s employee engagement programme (the Green Advocates’ Network) case as an antecedent to employees’ citizenship. To conduct the research the author put together a framework based on different literatures; that considers two manners in which corporations can be an arena: by providing the space in which employees can enact their citizenship; and by provoking change that result in citizenship. It uses concepts of status, entitlements and processes of participation as citizenship’s concepts; and awareness, behaviour and discourse and change’s stages to support the analysis and provide insights on the extent to which corporations can be arenas for citizenship.